THE EFFECTIVENESS OF THE DITAKOPUM APPLICATION IN FACILITATING PUBLIC SERVICES - Hidayati, Nur Laili; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of the DITAKOPUM (Digitalization of Cooperative and Micro Business Management) application as a means of facilitating public services in Sidoarjo Regency. Method: The research method used a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Results: The results show that in terms of achieving objectives, MSMEs obtained business legality more quickly and the number of officially registered businesses increased. In terms of accuracy of target, the application has targeted cooperatives and MSMEs, although some businesses in remote areas still experience obstacles in digital literacy and networking. In terms of quantity and quality of results, thousands of MSMEs have been registered with more organized and integrated data, although there are still input errors. In terms of efficiency, administrative services can be completed within 2–3 days at no cost. Meanwhile, in terms of adaptability, the application can be used for various types of businesses, with additional suggestions for marketplace integration and export features. Novelty: This research contributes new insights by directly assessing the effectiveness of the DITAKOPUM application as a digital innovation in the field of cooperative and micro-business management. These findings highlight the importance of digital literacy, technical support, and equitable infrastructure as key factors in optimizing the transformation of digital application-based public services